Agronomic Comparisons of Conventional and Organic Maize during the Transition to an Organic Cropping System - William J. Cox (Agronomy, 2018)
Maize producers transitioning to an organic cropping system must grow crops organically without price premiums for 36 months before certification. We evaluated conventional and organic maize with recommended and high seeding and N rates in New York to identify the best organic management practices during the transition. Conventional versus organic maize management differences included a treated (fungicide/insecticide) Genetically Modified (GM) hybrid versus a non-treated non-GM isoline; side-dressed synthetic N versus pre-plow composted manure; and Glyphosate versus mechanical weed control, respectively. Organic versus conventional maize yielded 32% lower as the entry crop (no previous green manure crop). Grain N% and weed densities explained 72% of yield variability. Organic and conventional maize, following wheat/red clover in the second year, yielded similarly. Organic maize with high inputs following wheat/red clover and conventional maize with high inputs following soybean in the third year yielded the highest. Grain N% and maize densities explained 54% of yield variability. Grain crop producers in the Northeast USA who do not have on-farm manure and forage equipment should plant maize after wheat/red clover with additional N (~56 kg N/ha) at higher seeding rates (~7%) during the transition to insure adequate N status and to offset maize density reductions from mechanical weed control.